El Excentrico, 1951-12-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2023)
December 20, 1951 [20 de diciembre de 1951] Ano 2, No. 4. Cover contains a photo of a young boy in formal attire, holding a rosary and a small copy of the bible. His hands are together in a prayer.